2020
DOI: 10.1002/ange.201916015
|View full text |Cite
|
Sign up to set email alerts
|

Iridium‐Catalyzed Silylation of Five‐Membered Heteroarenes: High Sterically Derived Selectivity from a Pyridyl‐Imidazoline Ligand

Abstract: The steric effects of substituents on five‐membered rings are less pronounced than those on six‐membered rings because of the difference in bond angles. Thus, the regioselectivities of reactions of five‐membered heteroarenes that occur with selectivities dictated by steric effects, such as the borylation of C−H bonds, have been poor in many cases. We report that the silylation of five‐membered‐ring heteroarenes occurs with high sterically derived regioselectivity when catalyzed by the combination of [Ir(cod)(O… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…This origin of selectivity contrasts with that we reported recently for the silylation of five-membered ring heteroarenes. 6 In our study of H/D exchange between the silane and these heteroarenes, the selectivity for H/D exchange at the least hindered C−H bond was lower than the selectivity for silylation at the least sterically hindered C−H bond. These data imply that the high selectivity for reactions of these less hindered substrates results from a slower rate for reductive elimination from a more hindered arylsilane than from a less hindered arylsilane.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…This origin of selectivity contrasts with that we reported recently for the silylation of five-membered ring heteroarenes. 6 In our study of H/D exchange between the silane and these heteroarenes, the selectivity for H/D exchange at the least hindered C−H bond was lower than the selectivity for silylation at the least sterically hindered C−H bond. These data imply that the high selectivity for reactions of these less hindered substrates results from a slower rate for reductive elimination from a more hindered arylsilane than from a less hindered arylsilane.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Meanwhile, the Hartwig group developed another efficient method for the silylation of five-membered heteroarenes using a sterically controlled strategy with the help of either a pyridine-imidazoline ligand ( 43 ) or a phenanthroline ligand ( 44 ) (Scheme 12 ). 23 Because of the acute bond angles in five-membered rings, the distance between the substituents is greater than those in six-membered rings, making the steric influence on the regioselectivity of five-membered heterocycles less pronounced. Mechanistic studies revealed that the rate of formation of C–Si bonds from isomeric heteroaryliridium complexes influences the selectivities of the silylation reactions more than the rates of the cleavage of carbon–hydrogen bonds during complex formation.…”
Section: Silylation Of C–h Bonds Through Organometallic Intermediatesmentioning
confidence: 99%